The Determinants of Organizational Commitment with Job Satisfaction as an Intervening Variable - Bokko, Nurdia; Noer, Elly; Chandrawati, Titi (Technium Social Sciences Journal, 2023)
This research aims to analyze the determinants of organizational commitment with job satisfaction as an intervening variable. The population in this study consisted of employees in the Class III Airport Operator Unit in the Merauke Papua region, totaling 139 employees, using purposive sampling technique. The study was conducted using a quantitative and qualitative approach, with SEM (Structural Equation Modeling) as the statistical tool. The results of the research show that work stress has a negative and significant effect on employee job satisfaction, while work motivation does not have a significant effect on employee job satisfaction. Work stress has a positive and significant effect on employee organizational commitment. Work motivation has a positive and significant effect on employee organizational commitment. Employee job satisfaction has a positive and significant effect on employee organizational commitment. Work stress has a negative and significant effect on employee organizational commitment through the intervening variable of job satisfaction and work motivation. Work motivation does not have a significant effect on employee organizational commitment through the intervening variable of job satisfaction at the Class III Airport Operator Unit in the Merauke Papua region.